Interaction effects of pig farming systems with educational level on performances of pig production systems in Manokwari District, West Papua-Indonesia - Desni T.R. Saragih; Deny Anjelus Iyai; Hans Mamboai; Dwi Nurhayati; Maria Arim; Stepanus Pakage; Ted Suruan (LPPM Perjuangan University of Tasikmalaya, 2021)
The aim of this research was to characterize pig farming system performances tethered under different agro-ecological zones in Papua. The field study was done in Manokwari regency and involved six districts, i.e. Nothern Manokwari district, Eastern Manokari District, Western Manokwari district, Warmare district, Prafi district and Masni district. Respondents chosen were guided by local extensionists, originated from 15 villages. Participatory situation analysis (PSA) was employed to approach pig farmers by using questionnaire. Pig body weights of piglets and growers were weighed except for mature pigs, body lengths and hearth girths were measured using tape. Herd number, number of piglets, adult pigs were recorded. A one-way analysis of variances was used. All data were entered in Excel and analyzed using SPPS version 10.0.. The findings shown that interaction between education and keeping systems occur on work hours and ages. Effect of education is significant on experience, location, and ethnic. In keeping systems, effect is real on experience, work hours, location, and ethnic. Interaction do not significant exist in number of pigs including see middle man, visited consumer, litter size, number of farrowing and income sources.